Anterior Teeth Mutilation and The Occurrence of Posterior Teeth Atrition in Siberut Island - Isnindiah Koerniati (Faculty of Dentistry, Universitas Indonesia, 2013)
The Mentawai ethnic group is accustomed to the practice of anterior teeth mutilation on males and females prior to reaching puberty age at Siberut Island, Mentawai Islands Regency, West Sumatra Province. Objective: of this research was to analyze the effects of anterior teeth mutilation on the teeth of the Mentawai ethnic, and prove that there is a correlation between anterior teeth mutilation and posterior teeth attritions. Material & method: There were 179 respondents who contributed to this study by applying accidental sampling method, consist of 96 respondents had anterior teeth mutilations and 83 non-mutilation respondents were found. Among respondents with anterior teeth mutilation, 53.07% of them had posterior teeth attritions. Only 0.56% of the respondent with anterior teeth mutilation did not have posterior teeth attrition. On the other hand, respondent without anterior teeth mutilation who got posterior teeth attritiona nd without posterior teeth attrition were almost similar (27.93% and 18.44%, respectively). Conclusion: the anterior teeth mutilation which is a ritual of Mentawai ethnic group and has been perfomred for generations, is significantly influent the occurrence of posterior teeth attrition. DOI: 10.14693/jdi.v16i2.96